Violence during the era of Zianid state in the Middle Maghreb (633-962H/1235-1554BC) – Assassinations as an example - - azibi, Zahwa (The Algerian Historical Journal, 2026)
The Zianid State durring its rule (633-962H/1235-1554BC) suffered from the Marinian bad behavior; as they attempted many times to dominate the scene. This led to violent clashes which caused many circumstances; probably violent manifestations and assassinations were the most noticeable. They also suffered inner conflicts between the sons of the Zianid home. These conflicts degenerated into assassinations hoping to reach power. All this, illustrates the black image of the history of the Zianid. And our aim is to know the manifestations of the violence practiced on the Zianids by the Marinids and the absence of any value of mercy during all the period of the rivalities between them, as well as to search for these practices among the sons of the Zianid family. We noticed that this general conflict generated a state of force and cruelty in the treatment and sovereignty of the bloody image.